Kemampuan Komunikasi Matematika Siswa melalui Penerapan Model Somatic, Auditory, Visualization, Intellectually (SAVI) - Saryantono, Buang; Nurdiana, Aty (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The research is based on the problem of low mathematical communication skills of eighth grade students of SMP Negeri 3 Bandar Lampung. The use of learning models that do not meet the learning needs of students is one of the reasons for the low ability. Therefore, this study aims to analyze students' mathematical communication skills through the application of the SAVI learning model. This research is a quasi-experimental study, with a population of all eighth grade students. The samples were two classes, namely students of class VIII C as the experimental class, which amounted to 33 students and class VIII H as the control class, which amounted to 32 students. The sample was determined by the Cluster Random Sampling technique. Students' mathematical communication skills are measured by tests that have been tested for validity and reliability. Hypothesis test using t test. The results of the hypothesis test show that tcount > ttable, thus it is found that the average mathematical communication ability that applies the SAVI model is higher than those who apply the conventional model. It can be said that there is an effect of the application of the SAVI model on the mathematical communication skills of eighth grade students of SMP Negeri 3 Bandar Lampung.